ECONOMIC INCLUSION AT THE INTERNATIONAL AND REGIONAL LEVELS: THE FINANCIAL ASPECT - PTASHCHENKO, Olena (Scientific journal «World of Finance», 2023)
Introduction. Economic inclusion at the international and regional levels refers to the active participation and integration of all individuals, communities, and countries into the global economy. It aims to ensure that no one is left behind and that economic opportunities and benefits are accessible to all, regardless of their socio-economic background, gender, ethnicity, or geographical location. By promoting economic inclusion at the international and regional levels, countries and organizations can foster economic growth, reduce inequality, and create a more inclusive and sustainable global economy. It requires collective efforts and a commitment to ensuring that the benefits of economic development are shared by all segments of society.The purpose of the article is to analyze the features of economic inclusion and its financial aspects, to form a set of effective tools to ensure financial inclusion in conditions of sustainable development.Results. The article analyzes and defines the main concepts of the research area: “economic inclusion” and “financial inclusion”, presents the main components of economic inclusion and defines the financial aspects of economic inclusion, which in the future provide an opportunity for the formation of financial inclusion. A conceptual approach to ensuring economic inclusion at the international and regional level, taking into account the financial aspect, has been formed.Conclusions. According to the results of the study, the need to ensure economic inclusion at the international and regional level has been proven, and the need to take into account the financial aspect of the development of inclusive economic relations has been proven. The presented results of the research make it possible to form the next steps regarding the study of the problems of economic inclusion in the aspect of the development of financial inclusion and to focus the vector of research precisely on the components of financial inclusion, as the main elements of ensuring the inclusiveness of the country’s economy in modern conditions of globalization and integration.